2017
DOI: 10.1038/s41598-017-07968-1
|View full text |Cite
|
Sign up to set email alerts
|

AmotL2 integrates polarity and junctional cues to modulate cell shape

Abstract: The assembly of individual epithelial or endothelial cells into a tight cellular sheet requires stringent control of cell packing and organization. These processes are dependent on the establishment and further integration of cellular junctions, the cytoskeleton and the formation of apical-basal polarity. However, little is known how these subcellular events are coordinated. The (Angiomotin) Amot protein family consists of scaffold proteins that interact with junctional cadherins, polarity proteins and the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Importantly AMOTL2, a binding partner of MAGI1, is required for the increased tumorigenicity of MAGI1-depleted luminal BCa cells, showing that AMOTL2 is a critical mediator in this context. AMOTs are apical scaffolds playing important roles in cadherin-based junction regulations and its linkage to the actin cytoskeleton 26,35,36 . Previous reports have shown that AMOTL1 is overexpressed in invasive ductal carcinomas, leading to invasive behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly AMOTL2, a binding partner of MAGI1, is required for the increased tumorigenicity of MAGI1-depleted luminal BCa cells, showing that AMOTL2 is a critical mediator in this context. AMOTs are apical scaffolds playing important roles in cadherin-based junction regulations and its linkage to the actin cytoskeleton 26,35,36 . Previous reports have shown that AMOTL1 is overexpressed in invasive ductal carcinomas, leading to invasive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells and in zebrafish developing embryos, AMOTL2 has been shown to link cadherins and the actin cytoskeleton. In particular, AMOTL2 is required for the maintenance of tension at the level of cadherin junctions to properly shape strong blood vessels 26,36 . Moreover, AMOTs are also known to control the Hippo tumor-suppressor signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Ras-interacting protein 1 (Rasip1) was also identified as a regulator of Rho GTPase signaling, and its loss resulted in excessive actomyosin contractility and improper Par3 localization ( 31 ). Interestingly, AmotL2 was also identified as a transcriptional target of YAP/TAZ and is known to act as a link between VE-cadherin and contractile actin filaments for lumen expansion to extend the lumen diameter ( 23 , 32 , 33 ). In vitro AmotL2 deletion inhibits EC migration and disrupts the vascular tube-like structure ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researches found that in AmotL2 i Δ EC mice, aortic constrictions were brought close to the ventricular outflow tract because of loss of actomyosin contractile forces. In addition, they discovered that Par3 is needed for localization of AmotL2 to VE-cadherin junctions to organize actin filaments for EC biological processes, such as lumen expansion ( 32 ). Hence, AmotL2 seems to be essential for proper lumen expansion; however, more detailed studies for lumen formation during vascular development are still required.…”
Section: Introductionmentioning
confidence: 99%
“…In endothelial cells and in zebrafish developing embryos, AMOTL2 has been shown to link cadherins and the actin cytoskeleton. In particular, AMOTL2 is required for the maintenance of tension at the level of cadherin junctions to properly shape strong blood vessels 26 , 36 . Moreover, AMOTs are also known to control the Hippo tumor-suppressor signaling pathway.…”
Section: Introductionmentioning
confidence: 99%